Impact of caudal fin geometry on the swimming performance of a snake-like robot. (1st February 2022) - Huang, Zhong; Ma, Shugen; Lin, Ziming; Zhu, Kaijia; Wang, Peng; Ahmed, Reza; Ren, Chao; Marvi, Hamid
Abstract: Eels and sea snakes are known for long migrations and high endurance cruising and can be great sources of inspiration for underwater robots. This study employs both computational and experimental techniques to explore the impact of caudal fin design on the swimming performance of a snake-like robot. The caudal fin geometry is systematically varied by changing the leading edge and trailing edge angles. Inspired by sea snakes, the robot mimics an anguilliform swimming gait. Robotic experiments and computational fluid dynamics (CFD) simulations are carried out with different caudal fin geometries. The results show that the snake-like robot achieves the best swimming speed and efficiency at an 85°leading edge angle and a 120°convex trailing edge angle. In addition, the numerical simulation results show that the wake structure formed by the snake-like robot consists of two parallel disconnected verse van Karman vortex rings. When the leading edge angle is slightly below 90°the body vortex merges and interacts with the caudal fin's vortex. This interaction contributes strongly to wake construction and significantly enhances swimming speed and efficiency. Highlights: In our study, we employ both computational and experimental techniques to systematically explore the impact of caudal fin design on swimming performance of a snake-like robot and to understand the underlying mechanisms. We find a caudal fin with a leading edge angle slightly lower than 90°and a mildly convex trailing edge enables the snake-like robot to exhibit superior swimming speed and efficiency. Finally, we analyze the propulsion mechanism of the snake-like robot through evaluating the wake structure and especially considering the interaction of body and tail wake structures.